The Effect Of Social Media Marketing Activities On Customer Response In Tiket.com - Viola De Yusa; Muhammad Saputra; Kadek Diantini (Proceeding International Conference on Information Technology and Business, 2020)
The purpose of this study was to determine the effect of social media marketing activity components on customer response in Tiket.com. This study was conducted on Tiket.com consumers who have already ordered a customer with a predetermined sample of 170 respondents. The analytical tool used Structural Equation Modelling (SEM). The result of this study indicated that social media marketing activities significantly affected consumer responses. Based on the results of the analysis, it was able to build strategies in social media marketing activities to have a high impact in increasing consumer response which is divided into behavioral responses referred to as electronic word of mouth and emotional responses called commitment.Keywords : Strategy, Customer Satisfaction, Service Quality, Product Quality